KAJIAN KUALITAS AIR DAN PENILAIAN KESESUAIAN TAMBAK DALAM UPAYA PENGEMBANGAN BUDIDAYA IKAN BANDENG (ChanoschanosForskal) DI DESA PEMUTERAN KECAMATAN GEROKGAK, KABUPATEN BULELENG - Suprabadevi Ayumayasari Saraswati; Alfi Hermawati Waskita Sari (Samakia : Jurnal Ilmu Perikanan, 2017)
Pemuteran Village is one of the villages in Gerokgak sub-district of Buleleng Regency which has big potential of aquaculture to be developed especially from milkfish enlargement activity in pond. The purpose of this research is to know the water quality condition of milkfish pond and to know the suitability of pond water quality in an effort to increase the profit of fish farming business (Chanos chanos Forskal) in Pemuteran Village. The research method used is purposive sampling. Data analysis used is scoring in the assessment of the suitability level of aquatic quality for fish breeding. Then the water assessment using matching method to compare the physics and chemistry of the waters of a location with the desired conformity criteria for milkfish cultivation.The result of the research shows that the condition of water quality of milkfish pond farming in Pemuteran Village is in optimal condition and included in the appropriate assessment (S1) based on the assessment of the suitability of water quality for the milkfish cultivation business.